El análisis financiero y su incidencia en la toma de decisiones en la gestión empresarial - Machare Calderón, Priscila Andrea (2015)
The objective of this project is develop a general analysis to the financial statements for the yeas 2013-2014 through the application of core indicators to amend problems and know the situation of the company COMPUXCELLENT CIA. LTDA dedicated to the sale of electronics and computer equipment. The methodology used for this investigation of the nature of quantitative approach, non-experimental, descriptive design, then using documentary techniques, interview and observation, requires a review of several theoretical foundations by different authors related to the preparation of a financial analysis. The process followed is able to demonstrate that the company do not apply tools of analysis to the financial statements, so that it was necessary to carry out a proposal that allows us to know the economic situation and financial performance of the company and in turn to help the management to be correct, obtaining as a real diagnosis results that will help the manager to make the right decisions for the fulfilment of the objective. It`s concluded that the financial analysis is a necessary tool and a key to the business management of the company and I recommend the use of this technique for all kind of companies regardless of the activity that you do.